Studies on forensically important entomological specimens recovered from monkey carrion exposed to different ecological habitats / Chen Chee Dhang - Chen, Chee Dhang (2012)
Little information was available on the forensically important specimens collected from carcasses in indoor and different ecological habitats in Malaysia. This study was attempted to determine the arthropod succession on carcasses (1) placed in different ecological habitats, such as lowland forested area, coastal area and montane forested area; (2) placed in indoor and outdoor conditions; and (3) carcasses being incinerated, submerged in freshwater river, and treated with insecticide and its effect on post mortem interval (PMI) estimation. Carcasses placed outdoor and indoor underwent 5 decomposition stages namely, fresh, bloating, decay, advanced decay and remains/dry. Decomposition duration on carcasses placed in indoor was prolonged, in comparison to outdoor in lowland forested and coastal areas by 1.67 to 2.73 folds, but not in montane forested area. There were no activity and oviposition of forensically important flies during nocturnal period. Flies activity were observed to be active from about 30 minutes after sunrise throughout the day until 10 minutes after sunset. There was no delay on flies oviposition on carcasses placed outdoor in all ecological habitats. However, there was at least a 1 day delay on PMI estimation on carcasses placed indoor in coastal area. It is interesting to note that there was a 3 days delay in PMI estimation on carcasses placed indoor in both lowland and montane forested areas. This study revealed the time required for blow flies to perceive the body and enter indoor to oviposit in three different ecological habitats. Our results established the time required to be added to estimate larval age to approach a realistic PMI estimation in this region. Oviposition of flies on carcasses, besides being used for PMI estimation, can also serve as geographical indicator: (1) Lucilia porphyrina was exclusively found in montane forested area; (2) Chrysomya nigripes was a strictly outdoor species and only invaded carcasses in lowland forested area; and (3) Chrysomya chani was only found invading carcasses placed in outdoor and indoor in lowland forested area. Study conducted on incinerated carcasses emphasizes that: (1) incineration effect does not deter the arrival and oviposition of flies; (2) incineration effect does not make any difference in the fauna succession pattern between incinerated and non-incinerated carcasses, with succession sequence from Calliphoridae, Sarcophagidae and Muscidae; and (3) decomposition rates on incinerated carcasses were faster than non-incinerated carcasses. Study conducted on carcasses submerged in freshwater river emphasizes that: (1) PMI estimation on carcasses submerged in freshwater river was delayed by a minimum period of 2 days; (2) there was no difference in the fauna succession pattern between carcasses submerged in freshwater river and placed outdoor, with the succession sequence from Calliphoridae, Sarcophagidae and Muscidae; (3) Chrysomya megacephala was the dominant adult flies observed visiting the carcasses, but only Ch. pinguis and Hemipyrelia spp. were found to be dominant maggots colonizing the carcasses; and (4) decomposition rates of carcasses submerged in freshwater river were slower than carcasses placed outdoor. Study conducted on carcasses treated with insecticide concluded that malathion repelled and delayed the insect invasions of the carcasses, especially flies for at least 7 days. Ants (Order: Hymenoptera) were reported occurring in all decomposition stages, and were not significant indicator for carcasses succession or PMI estimation. Beetles (Order: Coleoptera) were observed visiting the monkey carcasses in lowland and montane forested areas, and their succession on different decomposition stages were determined. No beetles were observed visiting carcasses placed in coastal area. More species of beetles were found in indoor than outdoor. Ants and beetles were found on carcasses strictly specific in certain geographical regions, indicating that they can serve as an evidence in forensic cases occurred in similar ecological habitats.